Critical Analysis of Albanian Criminal Legislation on Protection from Sexual Abuse - Aurela Anastasi; Agustela Nini-Pavli (Krytyka Prawa)
The approximation of the domestic legislation with the international legal frame-work is one of the main guarantees for the implementation of international standards. According to the Albanian Constitution, ratified treaties constitute part of the inter-nal juridical system and are implemented directly, except for cases when they are not self-executing, and the issuance of a law is necessary for their implementation. This article aims to analyse the alignment of Albanian criminal legislation with inter-national standards on prevention and fight against sexual violence. It seeks to achieve this through an approximation and comparative analysis of provisions of the Criminal Code with the international conventions ratified by the Republic of Alba-nia. Thanks to these methods, the paper has reached some important conclusions about the limited compliance of Albanian criminal provisions on sexual crimes with international standards and the need to approach them to international standards.